Implementasi Kebijakan Impor Barang Menggunakan Fasilitas ASEAN-India pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Palembang - Yudha Saputra; Ignasius Hendrasmo; Muhammad Abduh (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Implementation of the Policy on Import of Goods Using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office. This research aims to: 1) Implementation of the Policy on Import of Goods Using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office; 2) Describe and analyze the supporting and inhibiting factors for the Implementation of the Import of Goods Policy Using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office. This research uses research using a descriptive method is research that is directed to provide symptoms, facts, or events, systematically and accurately, regarding the characteristics of a certain population or region. In descriptive research, it is not necessary to look for or explain interrelationships by testing hypotheses. The results of the study show that: 1) Communication has been well established. Communication is carried out between fellow employees, related agencies/parties, and also with service users; 2) Resources are good and supportive, both in terms of infrastructure, training, and others. However, there are still shortcomings that must be followed up immediately, namely the need for competent employees in several fields, namely import duty revenue analysts and the lack of employees who specialize in handling import duties; 3) The attitude of the implementers can be said to be good, as evidenced by the seriousness of the policy implementers in carrying out the duties and mandates given, as well as the high commitment given by the policy implementers; 4) In the Implementation of the Policy on the Import of Goods Using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office, there are procedures that are passed in the import of goods using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office, and all are in accordance with existing regulations. Then in the activity of Importing Goods Using ASEAN-India Facilities at the Palembang Customs and Excise Supervision and Service Office, the SOP so far follows the SOP for Notification of Import of Goods. Another thing related to the organizational structure and the division of authority has all been well conceptualized and in accordance with the duties and functions of each policy implementer, so that there is no overlap in carrying out their duties.